Epstein-Barr Virus MicroRNA Expression Increases Aggressiveness of Solid Malignancies - Pandya, Deep (PLoS One, 2015)
The Cancer Genome Atlas (TCGA) microRNA (miRNA) initiative has revealed a pivotal role for miRNAs in cancer. Utilizing the TCGA raw data, we performed the first mapping of viral miRNA sequences within cancer and adjacent normal tissues. Results were integrated with TCGA RNA-seq to link the expression of viral miRNAs to the phenotype. Using clinical data and viral miRNA mapping results we also performed outcome analysis. Three lines of evidence lend credence to an active role of viral miRNAs in solid malignancies. First, expression of viral miRNA is consistently higher in cancerous compared to adjacent noncancerous tissues. Second, viral miRNA expression is associated with significantly worse clinical outcome among patients with early stage malignancy. These patients are also featured by increased expression of PD1/PD-L1, a pathway implicated in tumors escaping immune destruction. Finally, a particular cluster of EBV-miRNA (miR-BART2, miR-BART4, miR-BART5, miR-BART18, and miR-BART22) is associated with expression of cytokines known to inhibit host response to cancer. Quantification of specific viral miRNAs may help identify patients who are at risk of poor outcome. These patients may be candidates for novel therapeutic strategies incorporating antiviral agents and/or inhibitors of the PD-1/PD-L1 pathway.